Phased Response of the Subpolar Southern Ocean to Changes in Circumpolar Winds. Issue 11 (13th June 2019) - Naveira Garabato, A. C.; Dotto, T. S.; Hooley, J.; Bacon, S.; Tsamados, M.; Ridout, A.; Frajka‐Williams, E. E.; Herraiz‐Borreguero, L.; Holland, P. R.; Heorton, H. D. B. S.; Meredith, M. P.
Abstract: The response of the subpolar Southern Ocean (sSO) to wind forcing is assessed using satellite radar altimetry. sSO sea level exhibits a phased, zonally coherent, bimodal adjustment to circumpolar wind changes, involving comparable seasonal and interannual variations. The adjustment is effected via a quasi‐instantaneous exchange of mass between the Antarctic continental shelf and the sSO to the north, and a 2‐month‐delayed transfer of mass between the wider Southern Ocean and the subtropics. Both adjustment modes are consistent with an Ekman‐mediated response to variations in surface stress. Only the fast mode projects significantly onto the surface geostrophic flow of the sSO; thus, the regional circulation varies in phase with the leading edge of sSO sea level variability. The surface forcing of changes in the sSO system is partly associated with variations of surface winds linked to the Southern Annular Mode and is modulated by sea ice cover near Antarctica. Key Points: Variability in subpolar Southern Ocean sea level is documented using satellite radar altimetry, including in ice‐covered areas Subpolar Southern Ocean sea level exhibits a phased, bimodal response to circumpolar wind changes, entailing a strong seasonal cycle The relevant wind forcing is partially described by the Southern Annular Mode and is modulated by sea ice cover near Antarctica